Human Resources: Skills and Entrepreneurship in Industry 4.0 - Deri Firmansyah; Asep Achmad Rifa'i; Asep Suryana (PT FORMOSA CENDEKIA GLOBAL, 2022)
Increasing knowledge and competency challenges related to new technology and processes in Industry 4.0 (I4.0), a new strategic approach is needed for human resource management in companies. This study aims to identify a variety of skills that indicate an approach to how employees in companies and entrepreneurship can utilize them to face the emerging digital economy challenges in Industry 4.0. Macro environment analysis using the PESTEL framework approach was carried out. The finding that challenges in fulfilling the qualifications and requirements of employees and entrepreneurs who have a variety of skills to fulfill the core competencies in I4.0, requires the ability to identify needs, adjustments and flexibility with economic, social, technological and technical, environmental, and political and legal advances and changes . Identification and strategic approaches to qualifying core competencies that employees and entrepreneurship may require are explained in this article. Gap analysis of the categorization of each core competency and its evaluation is also described, ending with conclusions and recommendations.